Analisis Pengaruh Negatif Self Efficacy Siswa Jurusan Farmasi SMK Kesehatan Har-Kausyar - Dina Try Rahmadini; Intan Puspita Sari; Elza Rachman Panca Priyandalama (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
Trust or self-confidence (self-efficacy) plays an important role in the lives of students, as the main driver in improving self-quality. In this case there is a negative influence that can have a negative impact on a student's self-efficacy. The negative influence that can occur on a student's self-efficacy can be seen from the percentage of questionnaires administered with a descriptive qualitative analysis method. The subjects in this study were students majoring in pharmacy at the Har-kausyar Health Vocational School. The purpose of this study was to determine the negative effect of self-efficacy on students majoring in pharmacy at the Har-kausyar Health Vocational School. The results of the study show that there are several factors that can influence self-efficacy with a high percentage. This research is aimed at negative influences that can affect self-efficacy which differs from previous studies. Based on the results of the study, it was found that there were several factors that greatly influenced self-efficacy with a high percentage of self-concept and self-emotional variables.